Prognostic role of fibroblast growth factor receptor 2 in human solid tumors: A systematic review and meta-analysis - Gang Liu; Disheng Xiong; Rui Xiao; Zhengjie Huang (Tumor Biology, 2017)
In the past decades, the oncogenic role of fibroblast growth factor receptor 2 has been demonstrated in a number of cancer types. However, studies have reported contradictory findings concerning the correlation between fibroblast growth factor receptor 2 expression and prognosis in solid tumors. To address this discrepancy, we performed a meta-analysis with 18 published studies (2975 patients) retrieved from PubMed, EMBASE, and Web of science. Data were extracted and computed into odds ratios. The results showed that fibroblast growth factor receptor 2 overexpression was significantly associated with decreased 3-year overall survival (odds ratio = 1.93, 95% confidence interval: 1.30–2.85, p = 0.001) and 5-year overall survival (odds ratio = 1.62, 95% confidence interval: 1.07–2.44, p = 0.02) in patients with solid tumors. Subgroup analysis revealed that high fibroblast growth factor receptor 2 expression was also associated with poor prognosis of gastric cancer, hepatocellular carcinoma, and esophageal cancer, but not correlated with pancreatic cancer. In conclusion, fibroblast growth factor receptor 2 overexpression is correlated with decreased survival in most solid tumors, suggesting that the expression status of fibroblast growth factor receptor 2 is a valuable prognostic biomarker and a novel therapeutic target in human solid tumors.